Femoral hernia: sus complicaciones y recidivas - Croci, Fabio; Pérez Penco, Ernesto; Cordal, Adriana; Pereira, Jorge (Cirugía del Uruguay, 1984)
Femoral hernia is a pathology with well defined characteristlcs. lt occurs predominantly in aged patients with a high rate of mechanlcal complications and high morbimortality. With a poor follow up failures are around 10%. In our series there are 249 cases of femoral hernia separated in two differents groups. Clinical, pathological, therapeutical and evolutiva characteristics of this disease are analyzed. Sorne therapeutical conclusions for the management of this patients are done.